ATOMIC DECOMPOSITION OF μ-BERGMAN SPACE IN Cn - 张学军 席利华 范海霞 李俊锋 (Acta mathematica scientia, 2014)
Let μ be a normal function on [0, 1）. The atomic decomposition of the μ-Bergman space in the unit ball B is given for all p 〉 0.